Cation Mixing and Capacity Loss in Li||Ni0.6Mn0.2Co0.2O2 Cells: Experimental Investigation and Application of the Multi-Site, Multi-Reaction Model - Verbrugge, Mark W.; Baker, Daniel R.; Chen, Shuru; He, Meinan; Cai, Mei (Frontiers in Energy Research, 2022)
We clarify the degradation phenomena in a pouch cell that contains an insertion electrode (LizNi0.6Mn0.2Co0.2O2 or lithated NMC622) and a Li counter electrode. Greater than 500 cycles have been achieved in these cells employing 4 mAh/cm2 for both the initial Li metal negative and the NMC622 positive, and we find that cation mixing within the NMC622 is prevalent. That is, transition metals (Ni, and to a lesser extent, Mn and Co) in the transition-metal layer of NMC622 irreversibly exchange places with Li in the Li layer of NMC622, corresponding to a loss of Li sites and a concomitant loss of Coulombic capacity. The use of 1) a perturbation procedure of a recent publication employing the multi-site, multi-reaction model for the porous positive electrode and 2) a procedure to average the degradation phenomena over each cycle, which is shown to be consistent with slow degradation, simplifies the analysis of the experimental data and enables straightforward parameter regression. The resulting agreement between the model calculations and the experimental data is quite good, with the differences being similar to experiment-to-experiment variation.